Pengembangan dan Efektivitas Puzzlangsi: Media Pembelajaran Puzzle Berbasis ADDIE untuk Meningkatkan Hasil Belajar Siswa dalam Mata Pelajaran Sejarah Indonesia. - Nevada Atika Wildana; Satrio Wibowo; Muhammad Faris Abdil Aziz (Jurnal Artefak, 2026)
This study aims to develop and evaluate the feasibility of the Puzzlangsi learning medium in an effort to improve student learning outcomes in the subject of Indonesian History, specifically regarding the events leading up to the Proclamation of Independence. The method used is Research and Development (R&D) based on the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 36 eleventh-grade students at MA Darul Ulum Waru. Data collection was conducted through an expert validation questionnaire as well as pretest and posttest assessments. Data analysis included validity and reliability tests, as well as N-Gain calculations. The research results show that the media’s feasibility, as assessed by media experts, reached 86% and was categorized as “very good,” while the content validation scored 82.2% and received the same rating. All items in the instrument were deemed valid, with an r-calculated value greater than 0.329, and the instrument demonstrated a reliability coefficient of 0.755, which is considered high. Furthermore, the improvement in student learning outcomes showed an N-Gain score of 0.81, which falls into the high category. Therefore, the Puzzlangsi learning media is deemed suitable for use and effective in improving student learning outcomes on the topic of Events Leading Up to the Proclamation.